2013
DOI: 10.1002/adma.201301640
|View full text |Cite
|
Sign up to set email alerts
|

Wet Chemical Etching of Semipolar GaN Planes to Obtain Brighter and Cost‐Competitive Light Emitters

Abstract: Spotlight on etching: (11-22) semipolar GaN plane light-emitting diodes (LEDs) are demonstrated using a wet-etching process. A trigonal prism cell structure with a (0001) c plane and nnn{10-10} m planes is formed after KOH wet etching, and leads to a better ohmic contact and enhanced light extraction. LEDs fabricated by wet etching show excellent output performance 1.89 times higher than that of the reference LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…4a ). Details of the optical ray-tracing simulations can be found elsewhere 54 55 . The calculations showed that the 18% increase in the T op could lead to ~17% higher optical output power, indicating that another factor also contributed to the enhanced output power of the AgNW-LEDs.…”
Section: Discussionmentioning
confidence: 99%
“…4a ). Details of the optical ray-tracing simulations can be found elsewhere 54 55 . The calculations showed that the 18% increase in the T op could lead to ~17% higher optical output power, indicating that another factor also contributed to the enhanced output power of the AgNW-LEDs.…”
Section: Discussionmentioning
confidence: 99%
“…Photons that were emitted outside of the escape cone can be redirected back into the escape cone. The escape probability is increased to create a more efficient and, hence, a cost‐competitive product . A schematic view of this surface difference and the influence on photon out‐coupling is provided in Figure a ‐b .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the cause of LED chips failure is degradation of ohmic contacts associated with current crowding and generation of nonradiative recombination defects, while packaging materials deterioration results from modifications to their optical properties. Of these mechanisms, the generation of nonradiative recombination defects should be carefully considered because it is an intrinsic problem in materials properties, which requires a great deal of efforts and times to improve, whereas efforts to improve the device processes and the quality of packaging materials seemed to be more successful based on recent achievements .…”
Section: Introductionmentioning
confidence: 99%